Penerapan Penerapan Model Inkuiri Berbasis Pembelajaran Sosial Emosional untuk Meningkatkan Keterampilan Kolaborasi dan Prestasi Belajar Siswa kelas IV SDN Mojolangu 3 Malang: Penelitian - Mutamimaturrosyidah; Navik Khusniah; Aisyah Anggraeny; Budianto; Muh. Arafik (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Collaboration is one of the essential 21st-century skills that students must master to prepare for increasingly complex global challenges. Observations at SDN Mojolangu 3 Malang revealed that although learning activities involved group discussions, students’ collaborative skills had not been optimized. Some students were passive and merely copied answers from peers. This study aims to improve students’ collaboration skills and academic achievement through the implementation of an inquiry-based learning model integrated with social-emotional learning. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. Each cycle consisted of three stages: (1) Planning, (2) Action and Observation, and (3) Reflection. The results showed an increase in the implementation of the inquiry model from 85% to 100% by the teacher and from 80% to 98.3% by students, with a gain score of 1.00, categorized as a high improvement. Collaboration skill indicators also improved: Productive Work increased from a gain score of 0.04 (low) to 0.32 (moderate), Respecting Others from 0.11 to 0.32 (moderate), Compromise from 0.03 to 0.17 (still low), and Responsibility from 0.09 to 0.42 (moderate). Students' cognitive learning outcomes showed gain scores of 0.49 (from pre-cycle to cycle I) and 0.38 (from cycle I to cycle II), both categorized as moderate improvements.